Jawabanmu

2014-04-21T17:58:25+07:00
A. -5 

f(x) = ax+b
f(2) = 2a+b = 3
f(7) = 7a+b = 13
        ------------------   --
             -5a = -10
                a = 2

2a + b = 3
2(2)+b = 3
4+b = 3
b = 3-4
b = -1

jika     f(x) = ax+b
maka  f(-2) = 2(-2) + (-1) = -4-1 = -5

semoga membantu;;)
tunggu yaa, aku edit aja:)
ok
udah yaa:)
Komentar sudah dihapus
dari soal -_- liat deh, kan di soal yang kamu bikin f(2) = 3 dan f(7) = 13
2014-04-21T18:18:35+07:00
F(2)=2a+b=3…………………………………… f(7)=7a+b=13………………………………… -5a=-10…………………………………………… a=2…………………………………………………… 2a+b=3…………………………………………… 2*2+b=3………………………………………… b=3-4=-1……………………………………… f(-2)=-2*2+-1=-4-1=-5… (A)